Bina Damping Peningkatan Kapasitas Tata Kelola Administrasi Kependudukan Tingkat Rukun Tetangga se Kelurahan Kereng Bangkirai: Fostering Assistance to Increase the Capacity of Population Administration Governance at the Level of Neighborhood Harmony in Kereng Bangkirai Village - Jariah, Ainun; Nuswantoro, Setio Ardy; Ulfi, Muhammad; Wisne, Marga Tri Nuche; Bawi, Firdana; Rusita, Rusita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Effective population administration management is an important foundation in community development. Rukun Tetangga (RT) has a strategic role in managing data and providing administrative services. In Kereng Bangkirai Village, 23 Neighborhood Units are serving around 6,845 residents. However, administrative governance still shows shortcomings, such as low levels of education and understanding of administration as well as limited facilities and infrastructure. Urbanization triggered by the tourism potential in this area adds to the complexity of managing valid and up-to-date population data, especially in emergencies. Therefore, increasing the capacity of human resources at the level of RT is crucial. This community service program aims to provide training and assistance to the Chairman of the Neighborhood Units in population administration governance. This activity began with socialization about the importance of population data management, where the Population and Civil Registration Office provided material related to administrative services and digitalization. Furthermore, training on the use of Internet media and file storage in Google Drive was conducted, allowing participants to organize administrative files efficiently. The application of this technology is expected to improve partners' ability to manage documents, both physically and online. The results of this activity include a better understanding of population administration governance regulations and organized storage systems. This all contributes to improving community services and transparency in data management. In addition, support for facilities and infrastructure is also needed to improve administrative efficiency. Through collaboration between academics and the community, there will be an increase in public services and mutually beneficial synergy.